L’archevêque Lourenço Vicente et les partages héraldiques au Portugal à la fin du XIVe siècle - Seixas, Miguel Metelo (2022)
This text is about the heraldic usages of Lourenço Vicente, Archbishop of Braga and advisor of King John I of Portugal, interpreting them within the framework of medieval practices of sharing emblems, as a manifestation of solidarity and communion of projects or devotions. In the case in question, the symbolism and uses of the heraldic rose are highlighted, particularly in the Portuguese scene of the late fourteenth century.